WHY IS THE QUALITY OF TEACHERS IN INDONESIA SO POOR?: A CRITICAL DISCOURSE ANALYSIS ON GURU GEMBUL’S VIDEO - Nur Azizah; Sidik Prabowo; Abdul Muid; Aridah Aridah; Bibit Suhatmady (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In the context of Indonesian education, this research delves into the discourse surrounding the quality of teachers, focusing on the analysis of Guru Gembul's video content. By employing critical discourse analysis, the study aims to uncover the intricate interplay of identity, ideology, and social relationships as portrayed in the video. Through a deep exploration of language use and communication strategies, the research seeks to shed light on the underlying factors influencing teacher effectiveness and educational reform in Indonesia. The methodology involves a qualitative approach, utilizing thematic analysis of the video transcript and audience comments to reveal insights into the perceptions and challenges faced by teachers in the country. The findings highlight the significance of understanding how teachers construct their identities and ideologies through discourse, and how these constructions impact their interactions with students and the broader educational landscape. By bridging traditional textual analyses with multimedia communication, this study contributes to a nuanced understanding of the complexities surrounding teacher quality discourse in Indonesia, ultimately aiming to inform strategies for enhancing the quality of education and supporting teachers in their crucial role in shaping the future of Indonesian students.